2017
DOI: 10.3168/jds.2016-11323
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic effects of subclinical paratuberculosis (Johne’s disease) in dairy cattle

Abstract: The effect of subclinical paratuberculosis (or Johne's disease) risk status on performance, health, and fertility was studied in 58,096 UK Holstein-Friesian cows with 156,837 lactations across lactations 1 to 3. Low-, medium-, and high-risk group categories were allocated to cows determined by a minimum of 4 ELISA milk tests taken at any time during their lactating life. Lactation curves of daily milk, protein, and fat yields and protein and fat percentage, together with log-transformed somatic cell count, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…In our study, we observed a statistically significant decrease in the milk yield of seropositive animals in herd B (higher seroprevalence). A similar relationship was observed by Pritchard et al [6] in the UK and by Bates et al [15] in New Zealand. Conversely, in herd A (lower seroprevalence), we observed a significantly higher milk yield in seropositive than in seronegative cows.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, we observed a statistically significant decrease in the milk yield of seropositive animals in herd B (higher seroprevalence). A similar relationship was observed by Pritchard et al [6] in the UK and by Bates et al [15] in New Zealand. Conversely, in herd A (lower seroprevalence), we observed a significantly higher milk yield in seropositive than in seronegative cows.…”
Section: Discussionsupporting
confidence: 85%
“…The prevention and control of the epizootic status of the newly introduced animals is the only effective method of preventing MAP infections. The long disease incubation time, the absence of pathognomonic symptoms, and diagnostic methods characterised by variable sensitivity/specificity hinder correct JD diagnosis [4,6]. The disease appears in cattle herds worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…No fully effective tools or strategies exist to prevent new infections or disease progression. Effects of MAP on animal welfare are relevant and the effect on dairy operations has been linked to impaired udder health, milk production (McAloon et al, 2016;Pritchard et al, 2016;Smith et al, 2016), and reproductive performance (Donat et al, 2014;Mato et al, 2015;Pritchard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…JD control programmes have been implemented in most developed countries, with objectives based on the national economic situation of the cattle, sheep and goat industry and the herd‐level prevalence of MAP infection (reviewed by Kennedy, ; Geraghty, Graham, Mullowney, & More, ). In general, objectives include the following: (i) prove and protect freedom of disease at the country, regional or farm‐level, for example, in Norway (Whist et al., ), Sweden (Frössling et al., ) and northern and western Australia (Kennedy, ); (ii) protect export of milk or genetics, for example, Canada (McKenna, Vanleeuwen, et al., ); (iii) decrease prevalence of MAP infection and limit farm‐level economic losses, for example, Denmark (Nielsen, Jepsen, & Aagaard, ), the UK (Pritchard, Coffey, Bond, Hutchings, & Wall, ), Ireland (McAloon et al., ) and the USA (Wells, Hartmann, & Anderson, ); (iv) eliminate or reduce MAP load in bulk milk, for example, the Netherlands (Weber & van Schaik, ); and (v) eliminate MAP infection, for example, Norway in goats (Nagel‐Alne et al., ).…”
Section: Control Programmesmentioning
confidence: 99%